Sorghum genotype and particle size affect growth performance, nutrient digestibility, and stomach morphology in finishing pigs - Cabrera, M.R.; Bramel-Cox, P.J.; Hines, Robert H.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy pigs (average initial body wt of 119 lb) were used to determine the effects of sorghum genotype on milling characteristics, growth performance, nutrient digestibility, and stomach morphology in finishing pigs. The pigs were fed a corn-soybean meal-based control diet, with the corn (Pioneer 3377) milled to a mean particle size of 600 μm. Hard-endosperm sorghum (Pioneer 8585) and soft-endosperm sorghum (Pioneer 894) were milled to mean particle sizes of 800, 600, and 400 μm and substituted for the corn in the control diet on a wt/wt basis, so that the overall treatment arrangement was a 2 × 3 factorial plus control. The sorghums required less energy to grind, had greater production rates, and produced less noise during milling than the corn. Pigs fed the diets with hard and soft endosperm sorghum had average daily gain, average daily feed intake, and feed/gain similar to those fed corn. Pigs fed hard sorghum grew faster, but pigs fed soft sorghum were more efficient. As particle size was decreased, energy required for grinding increased and production rate slowed. Efficiency of gain and nutrient digestibility were maximized and excretion of nutrients as feces was minimized at 400 μm for both hard- and soft-endosperm sorghum. Considering the positive effects of fine grinding on efficiency of gain and nutrient digestibility, but the negative effects on energy required for milling, production rate and stomach morphology,an acceptable compromise for particle size of soft and hard sorghum in pelleted diets for finishing pigs will still likely be less than 600 μm.
Keywords: Swine; Sorghum; Process; Noise; Stomach; Digestibility; Finishing